2019
DOI: 10.1080/21505594.2019.1573050
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 induces rapid mucin transport, increases mucus thickness and quality and decreases colitis andCitrobacter rodentiumin contact with epithelial cells

Abstract: Citrobacter rodentium infection is a murine model for pathogenic intestinal Escherichia coli infection. C. rodentium infection causes an initial decrease in mucus layer thickness, followed by an increase during clearance. We aimed to identify the cause of these changes and to utilize this naturally occurring mucus stimulus to decrease pathogen impact and inflammation. We identified that mucin production and speed of transport from Golgi to secretory vesicles at the apical surface increased concomitantly with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 60 publications
(89 reference statements)
2
27
1
Order By: Relevance
“…In contrast, in a murine model of C. rodentium infection, the Th1 cytokines, IFN-γ, and TNF-α, decreased intestinal mucin production and its speed of transport from the Golgi to secretory vesicles. Lending further support to this finding, in vitro treatment of infected and non-infected intestinal mucosal surfaces with IFN-γ and TNF-α decreased the number of goblet cells, mucus thickness and transport (117). The contrasting data in the above paragraph implies that the effect of Th1 cytokines on mucin synthesis, transport, and secretion depends critically on, not only, the type of cytokine but also the pathological process in question.…”
Section: Adaptive Immunological Regulationmentioning
confidence: 72%
“…In contrast, in a murine model of C. rodentium infection, the Th1 cytokines, IFN-γ, and TNF-α, decreased intestinal mucin production and its speed of transport from the Golgi to secretory vesicles. Lending further support to this finding, in vitro treatment of infected and non-infected intestinal mucosal surfaces with IFN-γ and TNF-α decreased the number of goblet cells, mucus thickness and transport (117). The contrasting data in the above paragraph implies that the effect of Th1 cytokines on mucin synthesis, transport, and secretion depends critically on, not only, the type of cytokine but also the pathological process in question.…”
Section: Adaptive Immunological Regulationmentioning
confidence: 72%
“…As known, IL-4 is an anti-inflammatory cytokine which was illustrated with plenty of protective effects in colons, through the IL-4/signal transducer and activator of transcription 6 (Stat6) signaling pathway [54]. The increased IL-4 assists in inducing T helper 2 cell (Th2) responses, inhibiting Th17 cell development and polarizing macrophages toward M2 phenotype [54][55][56], and thus prompts its ability in maintaining the mucosal surface integrity, modulating intestinal immune responses and harboring the goblet cell functions [57]. Similar with IL-4, IL-10 was also reported to act as an antiinflammatory factor in the pathogenesis of UC [58].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed that the cytokine profile changes during the course of C. rodentium infection and is able to regulate mucus thickness and quality affecting bacterial localization relative to the epithelium in the distal colon of WT mice [39]. FPR2/Fpr2 is able to respond to both bacterial and endogenously released formylated peptides, to exert both pro-and antiinflammatory actions [40].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, relatively similar inflammatory cytokine responses were observed in the two genotypes at day 6 and 19 PI indicating that Fpr2 −/ − mice do not lack a protective response. However, the lower levels of TNF-α, IL-2, IL-6, and IL-13 in Fpr2 −/− mice during early infection might account for alterations related to mucus production and goblet cell function, decreased early host defense, and increased mucosal inflammation and pathogen dissemination, since cytokines affect these aspects [39,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%